Multicomponent systems with cyclodextrins and hydrophilic polymers for the delivery of Efavirenz. (5th October 2015) - Vieira, Alexandre Couto Carneiro; Ferreira Fontes, Danilo Augusto; Chaves, Luise Lopes; Alves, Lariza Darlene Santos; de Freitas Neto, José Lourenço; de La Roca Soares, Monica Felts; Soares-Sobrinho, Jose L.; Rolim, Larissa Araújo; Rolim-Neto, Pedro José
Highlights: Increase the aqueous solubility of Efavirenz. Formation of an inclusion complex with cyclodextrin. Formation of ternary systems with cyclodextrins and hydrophilic polymers. Characterizations of the ternary system in the solid state by SEM, DSC, TG, XRD, dissolution profile and FT-IR. Abstract: Efavirenz (EFZ) is one of the most used drugs in the treatment of AIDS and is the first antiretroviral choice. However, since it has low solubility, it does not exhibit suitable bioavailability, which interferes with its therapeutic action and is classified as a class II drug according Biopharmaceutical Classification System (low solubility and high permeability). Among several drug delivery systems, the multicomponent systems with cyclodextrins and hydrophilic polymers are a promising alternative for increasing the aqueous solubility of the drug. The present study aimed to develop and characterize in a ternary system of EFZ, MβCD and PVP K30. The results showed that the solid ternary system provided a large increase in the dissolution rate which was greater than 80% and was characterized by DSC, TG, XRD, FT-IR and SEM. The use of the ternary system (EFZ, MβCD and PVP K30 1%) proved to be a viable, effective and safe delivery of the drug. The addition of the hydrophilic polymer appeared to be suitable for the development of a solid oral pharmaceutical product, with possible industrial scale-up and with low concentration of CDs (cyclodextrins).